The Dilemma of Corporate Social Responsibility (CSR); Case Study of PT. Inco - Noorwahid Sofjan (Program Studi Pemikiran Politik Islam, Fakultas Ushuluddin, Adab, dan Dakwah IAIN Palu, 2021)
Since the CSR discourse has been widely discussed, the debate about the concept of CSR as an expression of moral responsibility and sensitivity to the social and environmental world has received resistance from some circles. The reason is that some people are trying to avoid CSR obligations. This paper talks about how the discourse and thinking about CSR struggles. Is CSR a voluntary activity for the company or is it an obligation (mandatory)? Then the authors describe the Indonesian context of CSR. And before the conclusion, the author tries to describe a case example of a CSR program run by a company in Indonesia and tries to analyze it from a human security perspective. As a result, from a human security perspective, the concept of CSR in Indonesia is still a problem. The cause, scholars are still trapped in efforts to formulate a detailed definition of CSR. As a result, practically the CSR program has not been seen as a humanitarian program. And it is still limited to a technical matter of fulfilling the company's procedural obligations.